(untitled) (Eurasian Research Bulletin, 2021)
The article discusses the main and most famous methods of teaching a foreign language. There are various methods of teaching a foreign language in the world. When teaching a foreign language, it is necessary to pay attention to new ways of stimulating the speech of students. Using new methods, you can easily learn to speak any foreign language and improve it.